Toleransi Beragama dalam Perspektif Islam - Baharuddin AR (2021)
As individual beings, humans have needs (biological, psychological and religious) and socially have the desire to adapt to the social environment. With the potential and abilities possessed, humans will try to actualize social needs and demands. Therefore, humans need other people with the aim of fostering social behaviors in the form of tolerance. Humans as religious beings crave peace and prosperity. Every religion teaches the values of tolerance. Islam is present as a religion that upholds the value of peace and harmony. Islam offers a concept of tolerance for differences which is called tasamuh, in tasamuh there are values of Rahmah (compassion), al-`Afw (forgiveness), al-Safh (forgiving), as-Salam (safety), al-`Adl ( justice), and al-Ihsan (kindness). Tolerance in this context is viewed from several aspects, namely theological, sociological and cultural. With tolerance, it is hoped that humans will be able to recognize diversity, including religious diversity or pluralism.